Pine ( Pinus densiflora ) needle extract could promote the expression of PCNA and Ki-67 after partial hepatectomy in rat - Lee,Gyeong Seok (2019)
Abstract Purpose To investigate the effects of pine needle extract (PNE) on the expression of proliferating cell nuclear antigen (PCNA) and Ki-67 during liver regeneration induced by 70% partial hepatectomy (PH) in rat. Methods Forty-eight male rats (SD, 7 weeks) had surgery (70% PH). They were randomly divided into two groups. PH + PNE group was only provided PNE diluted in water (10%) for drinking and PH group was provided water from 5 days before surgery to the time of sacrifice. PNE was made by pressing and filtering. Animals were sacrificed at 12h, 24h, 36h, 60h, 84h, 168h after PH, respectively. The expressions of PCNA and Ki-67 were determined as proliferation indices. Results Immunohistochemistry turned out to increase the expression of PCNA and Ki-67. PCNA expression of PH+PNE group increased up to twice of that of PH group. Western blot also seemed to increase the PCNA expression. These results indicated the promotion of cell proliferation in liver tissue and hepatic regeneration. Conclusions Pine needle extract stimulates the expression of some mitotic proteins during liver regeneration induced by 70% PH in rats. It suggests that administration of pine needle extract could accelerate the liver regeneration after partial hepatectomy.